Digitalization of Modules and Learning Tasks for Flexible, Convenient, And Safe Learning Experience of Students - Culajara, Carla Jobelle; Culajara, Juan Paolo Martin; Portos, Olivia; Villapando, Mark Kim (International Journal of Social Learning (IJSL), 2022)
The qualitative research design aims to explore the experiences of Grade 10 students as they were dealing with the new normal of education utilizing a digital modality. This study sheds light on other ways and means of learning and adapting to the modern world using technology. Based on the study's results, five superordinate themes have emerged: flexible, convenient, and safe learning environment, submission challenges, and innovation policy. The digital modality has a substantial impact on the learning of the students.  However, they sometimes have difficulty submitting outputs due to a slow internet connection. To reiterate, learning in digital modality is a great help student to in learning capabilities and adapting to change in education and being versatile in learning new different online platforms in simplifying the process and avoiding viruses to spread and becomes safe individual learns and further enhances learning in the modern world of education.